(untitled) (قضايا سياسية, 2023)
Human security has become not limited to the political, social and economic dimension only, but cultural security has become one of the important pillars in human life, society and the political system, and political culture represents one of the human manifestations regarding the political system and its impact on national security. As far as Iraq is concerned, the political change after 9/4/2003 revealed a cultural structural problem, and this problem may reach the point of a crisis, if the political cultures in Iraqi society mix, and most of them are traditional and submissive cultures that do not allow the establishment of a democratic civil society which led to a defect in the Iraqi national security.